Perencanaan Strategis Sistem Informasi Akademik Berbasis Android Di Universitas Jambi - Suratno, Tri (ReTII, 2018)
Jambi University is a State University located in Jambi. One of the College’s keys success factor is optimizing the use of technology and Information Systems. This requiresa good planning in the development of Information Systems (IS) and Information Technology (IT). Good planning strategy originated from a good SI / IT. In this research using Ward and Peppard method which includes analysis of business external environment, internal business analysis, external SI / IT analysis and internal SI / IT analysis. The analysis used is CSF analysis, SWOT analysis, Value Chain analysis, PEST analysis and McFarlan strategic grid analysis. The end result of this research is a portfolio of applications that must be developed to support the academic process at the University of Jambi. Karyword: Information Systems, planning strategy, Android,Ward and Peppard